2021
DOI: 10.4254/wjh.v13.i11.1534
|View full text |Cite
|
Sign up to set email alerts
|

Liver involvement in inflammatory bowel disease: What should the clinician know?

Abstract: Inflammatory bowel disease (IBD) may show a wide range of extraintestinal manifestations. In this context, liver involvement is a focal point for both an adequate management of the disease and its prognosis, due to possible serious comorbidity. The association between IBD and primary sclerosing cholangitis is the most known example. This association is relevant because it implies an increased risk of both colorectal cancer and cholangiocarcinoma. Additionally, drugs such as thiopurines or biologic agents can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 130 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…PSC may occur years after colectomy for UC, and UC may first develop after liver transplantation has been performed for PSC. 11,32 First-degree relatives of patients with PSC have more chance to develop PSC and ulcerative colitis (UC), supporting a genetic basis to these conditions. 11 Our patients did not have any family history of PSC and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…PSC may occur years after colectomy for UC, and UC may first develop after liver transplantation has been performed for PSC. 11,32 First-degree relatives of patients with PSC have more chance to develop PSC and ulcerative colitis (UC), supporting a genetic basis to these conditions. 11 Our patients did not have any family history of PSC and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, given the retrospective nature of the study, we cannot rule out possible biases related to data loss; furthermore, the wide observation period (2000–2013) may have led to non-homogeneous data collection over time. In addition, data on extraintestinal manifestations were not systematically available for all patients; though CD patients with liver involvement (such as primary sclerosing cholangitis) could have a phenotypical and clinical pattern that sharply differs from patients with CD alone [ 25 ]. For the abovementioned reason, we were not able to investigate this aspect in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that mice with increased human leukocyte antigen (HLA)-B27 fail to develop spondy-loarthritis when in a sterile environment, however this changes when commensal bacteria are introduced into their microbiome [24]. Beyond arthritis, IBD is associated with a variety of other autoimmune diseases including primary sclerosing cholangitis, type 1 diabetes (T1D), and even multiple sclerosis, all of which exhibit their own microbial alterations [25][26][27][28][29].…”
Section: -1950mentioning
confidence: 99%